Pengaruh Model Pembelajaran Langsung Berbantuan Media Laboratorium Terhadap Kreatifitas Fisika Siswa SMA - Ria Rizki Ekasari; Gunawan Gunawan; Hairunnisyah Sahidu (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2016)
This research aims to investigate the influence of direct instruction model with virtual laboratory media toward student creativity in physics using "pretest-posttest control group design". The creativity data collected by essay type test shows that pre-test average grade of experimental class is 41 and control class is 36, while post-test average grade of experimental class is 74 and control class is 69. Based on data analysis, creativity of male student in physics is higher than female student. The average grade of male student is 72 while female student is 70. The result of hypothesis testing using polled variance t-test with significance level of 5 % is tcalculation=> ttable = 1,99601 or, in other words, the calculated t value is greater than the value given in the table. It can be concluded that direct instruction model with virtual laboratory media influences high school student creativity in physics.